Hydro-mechanical behavior of two clayey soils in presence of household waste leachates - H. Yonli (GJESM Publisher, 2022)
BACKGROUND AND OBJECTIVESIn landfills, containment is provided by natural or artificial clayey materials known for their low permeability and for their pollutant retention capacity. However, the properties of these media are modified by leachates, whose migration they are supposed to limit. This study aims to reconsider the criteria for choosing suitable materials to make a bottom liner through both their long term hydraulic and mechanical performances.METHODSTwo fine materials sampled in Burkina Faso (West Africa) have been characterized in order to compare their hydro-mechanical behavior in the presence of household waste leachates. The first material is classified as an inorganic clay of low to medium plasticity according to Casagrande plasticity diagram, it is mainly kaolinitic with some traces amounts of smectites. The second one is classified clayey sand of low to medium plasticity, the predominant mineral clay being kaolinite. Hydro-mechanical tests were performed on both sampled materials to judge the sealing properties of these materials, as well as the characteristics of deformation and rupture which have an important effect to ensure the durability of a bottom liner. All these tests were performed first with distilled water then with leachates as interstitial fluids in order to understand the modification of the hydro-mechanical properties of the clayey soils.FINDINGSLeachate contamination always alters hydraulic properties of the materials. However, between the two soils, the most clayey and the most impervious (soils from Nouna) undergo the deeper weathering. Indeed, hydraulic conductivity of these soils in contact with a synthetic leachate increases from 1.71x10-10 to 1.51x10-9 m/s. In contrast to soils from Boudry, these soils also undergo very significant settlements over the long term with compressibility indexes varying from 0.164 to 0.225. For both soils, the shear strength increases showing that, from this point view, the leachate work in the sense of of the bottom liner stability. For soils from Nouna, the effective cohesion increases from 3 to 21 kPa with a slight decrease of friction angle; for soils from Boudry a slight increase of cohesion is noticed while friction angle increases from 34 to 37°.CONCLUSIONThis comparative study is of practical use to environmental geotechnics professionals because it shows that the choice in designing a bottom liner must be a compromise between long term hydraulic and mechanical behaviors of soils. It is also important to know the nature of the flows to contain in order to ensure the durability of the structure.